World, U.S. and Florida Avocado Situation and Outlook - Edward Evans; Sikavas Nalampang (EDIS)
The purpose of this article is to highlight the major trends and developments in the world, U.S., and Florida avocado industries. The analysis covers the post-WTO (World Trade Organization) implementation period from 1996 to 2005. This is EDIS document FE639, a publication of the Food and Resource Economics Department, UF/IFAS Extension. Published May 2006.